Rule based adaptive emotional solving web tutoring (AESWT) for kindergarden school on learning mathematics - Nurfatin, Nohadin (2013)
Rule Based Adaptive Emotional Solving Web Tutoring (AESWT) was develop to help the kindergarten student to solve they emotion problem when using web tutoring on mathematics. This AESWT focus on kids because nowadays we can see that the kids are more exposure and also as the higher percentage as user which use modern technology such as computer and smartphone. In addition, most of the tutoring for kids are using online. Therefore, systems that can resolve emotion problems among kindergarten student need to be developed in order to reduce that problem. The objective of the Adaptive Emotional Solving Web Tutoring (AESWT) system to be created is apply adaptive presentation technique for web tutoring. Seconds, developing prototype for adaptive emotional solving. Lastly, test the functionality of the prototype. This Adaptive Emotional Solving Web Tutoring (AESWT) will adapt in web tutoring mathematic. This AESWT function when received information about the emotional status of kindergarten student and it have the ability to change the Graphical User Interface based on emotion. In order to do that, this AESWT will use the rule based technique to match of human emotions with the right solutions. Besides that, this project using Macromedia Dreamweaver CS8 to develop Adaptive Emotional Solving Web Tutoring (AESWT). This AESWT, have three target emotion to solve which sad, happy, and angry. In addition, Adaptive Emotional Solving Web Tutoring (AESWT) will automatically help kids to solve they emotion easily during using a web tutoring on mathematics. The results for this prototype show that it can be a functionality when it can be change the interface to become more interesting and can be accepted by kindergarten kids. As the conclusion, AESWT system is can make kids feel comfortable and easily to solve emotional problem.